PENGARUH SUHU DAN LAMA PENGERINGAN TERHADAP KARAKTERISTIK TEH BUNGA TELANG (Clitoria ternatea L.) - Ayu Martini, Ni Ketut; Ayu Ekawati, Ni Gusti; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p09, 2020)
This study was conducted to determine the effect of drying temperature and time on the characteristics of blue pea flower tea and obtain drying temperature and time that produce blue pea flower tea with the best characteristics. The experimental design used was a factorial Randomize Block Design consisting of 2 factors: the first factor was drying temperature, namely 50oC, 60oC, and 70oC and the second factor was drying time, namely 3 hours, 3.5 hours, and 4 hours. The treatment was repeated 2 times to obtain 18 experimental units. The data obtained were analyzed by analysis of variance (ANOVA) and if the treatment had significant effect followed by Duncan test. The results showed that interaction between drying temperature and time had a significant effect on water content, extract content, total phenol, flavonoids, anthocyanin, and antioxidant activity. Drying at a temperature of 50oC for 4 hours was produced blue pea flower tea with the highest antioxidant activity (IC50) of 128.25 ppm, water content of 10.18%, extract content of 51.60%, total phenol of 515.48 mg/100g, flavonoids of 23.99 mg/100g, and anthocyanin of 249.69 mg/100g.